Organizational Communication and Cultural Identity in Turnover Intention Narratives Among Generation Z Minangkabau Migrants: A Qualitative Indigenous Psychology Study - Annisa Humaira; Zakwan Adri (Da'wa Faculty of Islamic State University Salatiga, 2026)
This study examines turnover intention among Generation Z Minangkabau migrants through the lens of organizational communication and cultural identity, employing a qualitative indigenous psychology approach. Communication dynamics, including how employees negotiate meaning, express workplace grievances, and construct cultural identity across organizational boundaries, are central to understanding turnover intention within this community. Using purposive sampling, 105 participants were selected based on criteria including Minangkabau ethnicity, West Sumatran origin, current employment status, residence outside West Sumatra, and Generation Z membership (born 1997–2012). Data were collected via open-ended qualitative surveys and analyzed through thematic analysis. Five themes emerged as communicative drivers of turnover intention: Career Development, Working Conditions, Income, Workload, and Family-Related Factors. These themes are interpreted through the cultural communication framework of merantau and the Minangkabau philosophy Adat Basandi Syarak, Syarak Basandi Kitabullah, revealing that turnover intention functions as a communicative act laden with cultural and spiritual meanings beyond mere job dissatisfaction. Notably, eleven participants reporting no turnover intention demonstrated value congruence achieved through effective organizational communication. This study argues that universal human resource management frameworks inadequately explain turnover communication among culturally distinct diaspora groups and that an interdisciplinary communication approach grounded in indigenous psychology offers stronger explanatory power for understanding how cultural values shape organizational communication behaviors among migrant workers.